Carcinogen-induced mutations in the mouse c-Ha-ras gene provide evidence of multiple pathways for tumor progression. - Brown, K (1990)
A number of mouse skin tumors initiated by the carcinogens N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), methylnitrosourea (MNU), 3-methylcholanthrene (MCA), and 7,12-dimethylbenz[a]anthracene (DMBA) have been shown to contain activated Ha-ras genes. In each case, the point mutations responsible for activation have been characterized. Results presented demonstrate the carcinogen-specific nature of these ras mutations. For each initiating agent, a distinct spectrum of mutations is observed. Most importantly, the distribution of ras gene mutations is found to differ between benign papillomas and carcinomas, suggesting that molecular events occurring at the time of initiation influence the probability with which papillomas progress to malignancy. This study provides molecular evidence in support of the existence of subsets of papillomas with differing progression frequencies. Thus, the alkylating agents MNNG and MNU induced exclusively G ---- A transitions at codon 12, with this mutation being found predominantly in papillomas. MCA initiation produced both codon 13 G ---- T and codon 61 A ---- T transversions in papillomas; only the G ---- T mutation, however, was found in carcinomas. These findings provide strong evidence that the mutational activation of Ha-ras occurs as a result of the initiation process and that the nature of the initiating event can affect the probability of progression to malignancy.